Peningkatan Kemampuan Kognitif Melalui Bermain Papan Angka Untuk Mengenal Lambang dan Konsep Bilangan 1-10 di Tk Dharma Wanita Semen - Maula, Fiya Zakiatul; Qalbi, Zahratul; Putera, Rafhi Febryan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Number board games are one of many game devices that can be used as an intermediary to improve children's mental activity at an early age or what is usually called cognitive ability. It is known that the learning model that is widely used in Early Childhood Education is the play while learning model. However, researchers found that the type of learning model applied by teachers at the Dharma Wanita Semen Kindergarten was still monotonous, so it had an impact on the development of cognitive abilities in group-A children, especially in terms of introducing the concept of numbers and the symbols for numbers 1 (one) to 10 (ten). Based on this, the researcher tried to develop cognitive abilities in group-A children in recognizing the concept of numbers and the symbols for numbers 1 (one) to 10 (ten) by using more varied media, namely the number board game. This research method is Classroom Action Research (PTK) using the John Elliot (1991) model which consists of 4 stages, including observation, planning, action and reflection. In this research, the implementation of the cycle was carried out in two cycles by repeating the same 4 stages in each cycle. In cycle 1 it was discovered that the percentage of success was still 68.5%, then the research continued in cycle 2 which showed a significant increase with a success percentage of 88.9%. The research results obtained show that the use of game devices with number boards can improve the cognitive abilities of group-A children at the Dharma Wanita Semen Kindergarten in recognizing the concept of numbers and symbols for numbers 1 (one) to 10 (ten).